Livestream Commerce: Dampak Daya Tarik Streamer terhadap Niat Beli Parfum Mykonos - Saviolla, Ariel Leonardo; Pakarti, Piji; Aqmala, Diana; Setiawan, Aries (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study examines the effect of TikTok Live streamer attractiveness on the purchase intention of Mykonos perfume among Generation Z in Semarang, with trust and attitude as mediating variables. A quantitative method was used, involving 150 respondents through purposive sampling. Data analysis was conducted using the SEM-PLS approach with SmartPLS version 4.0 software. The results show that streamer attractiveness has a significant positive effect on trust and attitude, which subsequently drive purchase intention. However, streamer attractiveness has no direct effect on purchase intention. This finding confirms a full mediation phenomenon, where the streamer's charm effectively triggers purchases only if it successfully builds trust to reduce blind buy risks and forms a positive audience attitude.